A Computational Reproduction of "Intrinsic Information Preferences and Skewness" by Masatlioglu, Orhun and Raymond (2023) - Romain Gauriot; Yang Liu; Jack McLaughlin; Joshua B. Miller (Institute for Replication (I4R), 2024)
Masatlioglu et al. (2023) show a strong intrinsic preference for positively skewed information over negatively skewed information through three laboratory and two field experiments. Using the provided replication package, we successfully computationally reproduce these results. Additionally, we test the robustness of the findings by employing alternative statistical tests, which confirmed the original conclusions. We also make minor comments about the paper that may be useful to researchers building on Masatlioglu et al. (2023)'s work.
Keywords: 330; replication; information preferences; skewness; information avoidance